2021
DOI: 10.1088/1402-4896/ac454d
|View full text |Cite
|
Sign up to set email alerts
|

Improving photoluminescence, optical and electrical characteristics of PMMA films with gamma irradiation

Abstract: Polymeric materials are macromolecules, essentially a combination of numerous repeated subunits. Polymers are innovative and advanced materials that currently have a strong impact on our daily lives. In recent years, polymer use has been prominent due to the materials’ distinctive properties; thus, they entered different fields of science, technology and industrial-biomedical applications.The improvement of photoluminescence, optical and electrical characteristics of non-conducting Poly(methyl methacrylate) (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The experimentally and theoretical FTIR spectra registered of polycarbonate structure are depicted in Fig. (4).…”
Section: Molecular Modeling Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimentally and theoretical FTIR spectra registered of polycarbonate structure are depicted in Fig. (4).…”
Section: Molecular Modeling Calculationsmentioning
confidence: 99%
“…Three distinct processes are involved in luminescence: (a) excitons, or electron-hole (e-h) pairs, are excited by an external energy source; (b) the e-h pairs are thermalized toward thermal or epithermal equilibrium, and (c) the thermalized pairs undergo radiative recombination to generate electromagnetic emission. The recombination of excitons or band-to-defect level or band-toband transitions is commonly associated with peaks in the photoluminescence spectrum [4,15]. The radiative-recombination of the thermalized pairs of electron-hole (e-h) occurs in this technique as a result of the excitation and transfer of energy into the chromophoric sites [14].…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(methyl methacrylate), PMMA, also known as acrylic, is a stiff polymer that exhibits interesting hardness, optical clarity, and abrasion resistance. As a result, it is used a lot in micro-photonics, optical lenses and devices, solar cells instead of glass, dosimetry, alpha particle detection, and as a base for nanofillers to block gamma-rays and UV light 9 . Cao et al 1 reported that the PMMA mixed with 15.6–44 wt% Bi 2 O 3 particles showed good blocking γ-rays with energies up to 1 MeV.…”
Section: Introductionmentioning
confidence: 99%